2014
DOI: 10.3892/ijmm.2014.2038
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A upregulates the protein expression of OX1R and enhances the proliferation of SGC-7901 gastric cancer cells through the ERK signaling pathway

Abstract: Orexins are hypothalamic peptides that regulate food intake, wakefulness, the reward system and energy metabolism. Recent studies have demonstrated the ability of orexins to promote a robust apoptosis and subsequent inhibition of cell growth in various types of cancer cells. The present study was conducted to investigate the effects of orexin A on the survival of human gastric cancer cells, SGC‑7901, and the possible mechanisms. SGC‑7901 cells were exposed to various concentrations of orexin A in vitro in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
0
26
0
3
Order By: Relevance
“…OX1R was also identified in cortical adenomas but its relation to apoptosis was not investigated ( 88 , 89 ). In human hepatocellular carcinoma tissues ( 90 ), in gastric cancer cell lines, SGC-7901 and BGC-823, OxA seemed to enhance the proliferation and inhibited the apoptosis which is mediated by the ERK or AKT signaling pathway ( 91 , 92 ), respectively. Moreover, OxA and cholecystokinin (CCK) inhibited the migration of colorectal cancer cell line, HT-29 mediated by heterodimerization of OX1R and CCK1R ( 93 ).…”
Section: Other Cancersmentioning
confidence: 99%
“…OX1R was also identified in cortical adenomas but its relation to apoptosis was not investigated ( 88 , 89 ). In human hepatocellular carcinoma tissues ( 90 ), in gastric cancer cell lines, SGC-7901 and BGC-823, OxA seemed to enhance the proliferation and inhibited the apoptosis which is mediated by the ERK or AKT signaling pathway ( 91 , 92 ), respectively. Moreover, OxA and cholecystokinin (CCK) inhibited the migration of colorectal cancer cell line, HT-29 mediated by heterodimerization of OX1R and CCK1R ( 93 ).…”
Section: Other Cancersmentioning
confidence: 99%
“…OX1R mRNA was expressed in the following cell lines: BGC-823 12 and SGC-7901. 13 OX2R mRNA was not expressed in either of these cell lines. 12 , 13 …”
Section: Resultsmentioning
confidence: 74%
“…However, recent results showed that OXA can enhance proliferation of rat insulinoma or SGC-7901 human cancer gastric cells. 27,29,30 Noteworthy, in all studies, orexin concentrations as well as times of incubations were very similar. Overall, stimulation of cell death in cancer cells is not general, and cell specific effects of OXA may be possible.…”
Section: Discussionmentioning
confidence: 99%